Hydrogen Bonds, Halogen Bonds, and Other Non-Covalent Interactions in a Series of Iodocymantrenes [Mn(C5InH5−n)(CO)2L], L = CO, PPh3, and n = 1–5 - Christian Klein-Heßling; Karlheinz Sünkel (Inorganics)
In this study, the molecular and crystal structures of iodocymantrenes [Mn(C5InH5−n)(CO)2(PPh3)] (1b n = 1; 2, n = 2; 3, n = 3) are reported and compared with the known structures of [Mn(C5InH5−n)(CO)3] (1a, n = 1; 5, n = 5) and [Mn(C5I4H)(CO)2(PPh3)] (4). In the crystals, many weak interactions like H bonds (H…O, H…I, H…π), halogen bonds (I…I, I…O, I…C, I…π), and π-π contacts are found. Hirshfeld analyses show that H bonding is far more important when the PPh3 ligand is present, and this is mainly based on dispersive interactions. However, without the PPh3 ligand, H…I and other I…X contacts are the most frequently observed intermolecular interactions.